Sistem Informasi Penjualan Toko Parfum Berbasis Website - Geges, Septian; Raihan Luthfiansyah Effendy Ekapatra (STEKOM PRESS, 2024)
This research aims to design a website-based online store by utilizing a recommendation system with content-based filtering. The recommendation system is useful to help buyers get product suggestions that are in accordance with their preferences. The development method used in this research is the Waterfall model with the stages of needs analysis, design, program code generation, and testing. Researchers also use the UML model to help design the system and use the Laravel framework for website development. Based on the results of this study, the online store system designed has benefits for customers, because they can shop anywhere without having to come to the store directly. The recommendation system used also helps customers in choosing perfumes that match their preferences.